The twentieth century in European memory transcultural mediation and reception - Sindbæk Andersen, Tea 1974-; Törnquist-Plewa, Barbara 1960- (Brill, 2017)
The Twentieth Century in European Memory' investigates contested and divisive memories of conflicts, world wars, dictatorship, genocide and mass killing. Focusing on the questions of transculturality and reception, the book looks at the ways in which such memories are being shared, debated and received by museum workers, artists, politicians and general audiences. Due to amplified mobility and communication as well as Europe?s changing institutional structure, such memories become increasingly transcultural, crossing cultural and political borders. This book brings together in-depth researched case studies of memory transmission and reception in different types of media, including films, literature, museums, political debate printed and digital media, as well as studies of personal and public reactions
Keywords: Geschichte 1913-2000; Kollektives Gedächtnis; Interkulturalität; Krieg; Europa; Aufsatzsammlung